Identifying the factors impacting upon personal tax compliance : a study involving tax affairs officers of Malaysian businesses - Nivakan, Sritharan; Salawati, Sahari; Sharon, Cheuk Choy Sheung; Mohamed Ahmad, Syubaili (School of Accounting, Auditing and Taxation, UNSW, 2022)
It is assumed from the literature reviews in taxation that a tendency for tax non-compliance exists among the officers who deal with tax matters in their business establishments in Malaysia when they do not comply with their respective tax systems. The hitherto published studies have not yet explored the tax compliance behaviour of tax affairs officers. Given this gap in the literature, this study endeavours to investigate the factors that impact corporate tax affairs officers’ personal tax compliance behaviour in Malaysia. Using purposive and snowball sampling techniques, the data was collected from 392 tax affairs officers of businesses in Malaysia. SmartPLS is used to analyse the data and test the hypotheses. The findings of this study reveal that peers’ tax compliance, audit probability, service quality of tax authority, and satisfaction with government spending strongly impact upon personal tax compliance behaviour of corporate tax affairs officers. This study opens a gateway to producing extensive and expeditious empirical evidence that could support the relation between tax affairs officers’ personal tax compliance and their decision-making on corporate tax compliance.